Images of War in Late Victorian War and Adventure Novels for Children - Dorothea Flothow (Cahiers Victoriens et Edouardiens)
The late-Victorian fascination with war and the military was mirrored in the period’s children’s fiction which presented war as an exciting spectacle and a glorious adventure. Through a number of formulized conventions and strategies, the narratives downplay the dangers of war and stress the inevitability of British victories. Although the most prominent of these strategies, the “war-games metaphor,” which trivialized war by comparing it to a football or a cricket match, has been examined by a number of studies, little attention has so far been paid to other conventions of the genre which also serve to familiarize war and suggest its basically harmless nature: the characterization of the novels’ prototypical English boy-hero; their formulaic plot and conventionalized cast; the way the novels remember Britain’s glorious military past to predict her equally victorious future; or the ways by which military defeats and difficulties are glossed over. Yet the question of how war was presented to the future generation seems of particular relevance, for not only does children’s fiction mirror contemporary ideas and values, it is also seen as an important means of shaping and creating them. By analysing a selection of about 70 children’s novels of the most well-known authors of the genre, this paper therefore proposes to examine the image of war created and the conventions used to describe war to a child readership. Although the majority of these novels were written for boys, a number of girls’ novels will also be analysed, for female characters were also given a more active role in the boys’ novels of the 1890s.